Interictal high-frequency oscillations generated by seizure onset and eloquent areas may be differentially coupled with different slow waves. Issue 6 (June 2016) - Nonoda, Yutaka; Miyakoshi, Makoto; Ojeda, Alejandro; Makeig, Scott; Juhász, Csaba; Sood, Sandeep; Asano, Eishi
Highlights: Interictal HFOs were noted in seizure-onset and sensorimotor–visual sites during sleep. Epileptogenic HFOs may be more preferentially coupled with slow waves of 3–4 Hz. Physiologic HFOs may be more preferentially coupled with slow waves of 0.5–1 Hz. Abstract: Objective: High-frequency oscillations (HFOs) can be spontaneously generated by seizure-onset and functionally-important areas. We determined if consideration of the spectral frequency bands of coupled slow-waves could distinguish between epileptogenic and physiological HFOs. Methods: We studied a consecutive series of 13 children with focal epilepsy who underwent extraoperative electrocorticography. We measured the occurrence rate of HFOs during slow-wave sleep at each electrode site. We subsequently determined the performance of HFO rate for localization of seizure-onset sites and undesirable detection of nonepileptic sensorimotor–visual sites defined by neurostimulation. We likewise determined the predictive performance of modulation index: MI(XHz)&(YHz), reflecting the strength of coupling between amplitude of HFOsXHz and phase of slow-waveYHz . The predictive accuracy was quantified using the area under the curve (AUC) on receiver-operating characteristics analysis. Results: Increase in HFO rate localized seizure-onset sites (AUC ⩾ 0.72; p  < 0.001), but also undesirably detected nonepileptic sensorimotor–visual sites (AUC ⩾ 0.58; p  < 0.001). Increase in MI(HFOs)&(3–4Hz) also detected both seizure-onset (AUC ⩾ 0.74; p  < 0.001) and nonepileptic sensorimotor–visual sites (AUC ⩾ 0.59; p  < 0.001). Increase in subtraction-MIHFOs [defined as subtraction of MI(HFOs)&(0.5–1Hz) from MI(HFOs)&(3–4Hz) ] localized seizure-onset sites (AUC ⩾ 0.71; p  < 0.001), but rather avoided detection of nonepileptic sensorimotor–visual sites (AUC ⩽ 0.42; p  < 0.001). Conclusion: Our data suggest that epileptogenic HFOs may be coupled with slow-wave3–4Hz more preferentially than slow-wave0.5–1Hz, whereas physiologic HFOs with slow-wave0.5–1Hz more preferentially than slow-wave3–4Hz during slow-wave sleep. Significance: Further studies in larger samples are warranted to determine if consideration of the spectral frequency bands of slow-waves coupled with HFOs can positively contribute to presurgical evaluation of patients with focal epilepsy.